High-strength high-toughness low temperature steel for ship and manufacture method thereof - YE QIBIN; YANG YU; HAO SEN; YAN LING; ZHANG CHAOFENG; ZHOU CHENG (2013)
The invention discloses high-strength high-toughness low temperature steel for ship and manufacture method thereof. The steel is composed of (by wt%) C 0.04-0.12, Si 0.20-0.55, Mn 0.8-1.4, P 0.005-0.015, S less than or equal to 0.005, Als 0.02-0.07, N less than or equal to 0.005, Cu 0.05-0.40, Ni 0.05-0.50, and Fe and unavoidable impurity in balance, with Ni/Cu of 1.2-1.5; and one or more than two of Nb 0.005-0.03, Ti 0.005-0.02, Ca 0.001-0.006, and Mg 0.0005-0.002. The steel has advantages of low compression ratio, high strength, good low temperature impact energy, good texture uniformity, and good elongation, to ensure low hardenability and cold crack resistance of repair welding heat-affected zone even if under polar climate condition.